2008
DOI: 10.1016/j.juro.2007.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity in Patients With Urolithiasis and its Prognostic Usefulness in Stone Recurrence

Abstract: This study reveals that obesity is associated with metabolic alterations and urinary stone recurrence. Weight control may be considered one of the preventive modalities against recurrent stone formation, especially in first time stone formers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 17 publications
1
49
1
Order By: Relevance
“…The superobese patients also suffered from higher degrees of comorbidity than their overweight or ideal weight counterparts and had a higher proportion of uric acid stones, a finding consistent with reports from other investigators. 22 Despite these facts, surgical outcomes did not differ. Furthermore, overall complication rates and severity were comparable between BMI groups indicating that PCNL can be safely performed even at BMI extremes.…”
Section: Discussionmentioning
confidence: 96%
“…The superobese patients also suffered from higher degrees of comorbidity than their overweight or ideal weight counterparts and had a higher proportion of uric acid stones, a finding consistent with reports from other investigators. 22 Despite these facts, surgical outcomes did not differ. Furthermore, overall complication rates and severity were comparable between BMI groups indicating that PCNL can be safely performed even at BMI extremes.…”
Section: Discussionmentioning
confidence: 96%
“…The development of insulin resistance might decrease urinary excretion of ammonium and renal ammoniagenesis with ensuing lower urinary pH. Persistently lower urinary pH can induce the formation of uric acid and mixed urate-calcium oxalate stones [ 19 ] . In the present study, in 16.4% of patients with metabolic syndrome, mixed uric acid and calcium oxalate stones were detected.…”
mentioning
confidence: 99%
“…37 Multivariate regression modeling stratified by stone incidence has shown that obesity is the only strong predictor of stone recurrence in first-time stone formers. 30 No association between obesity and stone recurrence has been detected in recurrent stone formers, suggesting a different mechanism in this group of patients. Interestingly, weight loss has been advocated not only as a recommendation to modify stone risk factors but also as a treatment for obesity-related glomerulopathy.…”
Section: Obesity and Renal Stone Diseasementioning
confidence: 79%
“…No association between obesity and stone recurrence was detected in recurrent stone formers. 30 Semins et al 24 reviewed data from a 5-year period (2002-2006) in a national private insurance database to identify subjects diagnosed with or treated for kidney stones. From a dataset of 95,598 patients, gender distribution of the 3257 stone formers was 42.9% male and 57.1% female.…”
Section: Obesity and Renal Stone Diseasementioning
confidence: 99%